Nuclear maturation of immature bovine oocytes after vitrification using open pulled straw and cryotop methods - Hajarian, Hadi; Haron, Abd Wahid; Yusoff, Rosnina; Daliri, Morteza; Dashtizad, Mojtaba; R., Holmes; Othman, Abas Mazni (Academic Journals, 2011)
To date, at least two well known methods have been widely used for vitrification of oocytes and embryos at different stages in a variety of species. However, there is no reported data regarding the comparative effectiveness of these two methods for vitrification of immature bovine oocytes. The objective of this study is to compare the nuclear maturation of immature bovine oocytes vitrified using open pulled straw (OPS) and cryotop methods. Two experiments were conducted in this study. In the first experiment, cytotoxicity of vitrification solutions (VS) from both methods was studied. After removal of cryoprotectants, cumulus oocyte complexes (COCs) was cultured in vitro and cleavage rate was monitored on Day 2 post-insemination (pi), whereas, morulae and blastocyst yields on Days 5 and 8 pi, respectively. The VS solutions significantly reduced zygotic cleavage rate, morulae and blastocyst rates compared with the control group (P < 0.05). The lowest cleavage rate resulted from prolonged exposure time to OPS-VS solutions (35.1%; P < 0.05). However, the morulae and blastocyst rates were significantly higher (P < 0.05) for embryos derived from oocytes exposed to cryotop solutions (40.5 and 22.4%, respectively). In the second experiment, effectiveness of both vitrification methods was compared for cryopreservation of immature bovine oocytes. After warming, COCs were cultured in vitro for 24 h. The polar body (PB+) and metaphase-II (MII) stage rates differed significantly among treatment groups. Oocytes vitrified using cryotop solution and device showed higher percentages of PB+ (36%) and MII (51%) rates. In addition, the lowest percentage of degenerated oocytes resulted from cryotop solution. The highest degenerated oocytes obtained by equilibration in OPS solution and vitrified using OPS device (40%; P < 0.05). In conclusion, our data demonstrated that cryotop solution was less toxic to the immature bovine oocytes and vitrification with the cryotop method resulted in higher survival and nuclear maturation rates.